Teacher in the situation of setting a learning task - E.V. Chudinova (Культурно-историческая психология)
Context and relevance. The concept of learning task is the most important in the theory of learning activity. At the same time, most of the research on the processes of setting and solving learning tasks focuses on the learner's side. The majority of research on the processes of setting and solving learning tasks is focused on the pupil's side, despite the conceptual ideas about the total action in the mediating situation. Objective. To consider the situation of setting and solving a learning task from the perspective of the teacher organizing the situation. Hypothesis. The teacher's reference systems in the process of setting a learning task are complex and contradictory, and they cannot be fully defined during the preparation for the lesson before trying it out in real interaction. The condition for the emergence of cumulative action in solving a learning task is a special authorial position of the teacher. Methods and materials. Five teachers (women from 28 to 54 years old, experience in the D.B. Elkonin—V.V. Davydov system from 2 to 16 years) took part in the case study. They included observation and analyses of video recordings of 7 cases of one learning task (the task of discovering isolines, Year 3, course «World around us»). In addition, a questionnaire was administered to teachers at the refresher training courses (10 teachers who had experience in setting this learning task and 10 who had no such experience) in order to assess teachers' understanding of the technology of setting the task after reading the methodological manual. Results. The methodological manual is sufficient for teachers to create a full-fledged lesson project, it is read and understood equally by teachers with and without experience in setting this learning task (Fi-Fisher and V-Kramer criteria). Teachers' difficulties in setting the learning task are related to the contradictory and dynamic nature of the orientations. The effectiveness of teacher-pupil interaction at key moments of setting and solving a learning task is determined not only by the teacher's sensitivity to children's actions, but also by the teacher's focus on the relationship of children's actions to the general method being reconstructed. Conclusions. The situation of successful formulation and solution of a learning task can be considered as a situation of cumulative action, and at the teacher's side - as a productive authorial action. The teacher's sensitivity to the current children's actions in their relation to the reconstructed method and the teacher's special authorial position are the conditions for the coherence of the pupils' and teacher's positions. The teacher's own supports in the situation of setting and solving a learning task are built as a result of testing and comprehension of the guidelines given in the methodological manual and transformed at the stage of designing a staged lesson.